ESTIMATION OF NUMBERS OF COLIFORM BACTERIAL AS WATER QUALITY INDICATOR IN KEPAHIANG DISTRICT RIVERS, BENGKULU PROVINCE - Sipriyadi Sipriyadi; Risky Hadi Wibowo; Welly Darwis (Universitas Medan Area, 2021)
Coliform is a group of microbes that are used as indicators of water quality. Water pollution is generally caused by pathogenic microbes from feces, household waste, and industrial activity waste. This study aimed to estimate the total number of coliform contamination in several rivers in Kepahiang Regency, namely Tebat Monok (TM), Sempiyang (SPY), Penanjung Panjang (PP), Embong Ijok (EI) Air Langkap(ALK), and Air Belimbing (ABB). Total coliform and Fecal coliform tests were carried out using the Most Probable Number (MPN) method on Lactose Broth, Brillian Green Lactose Bile Broth and pour plates on Eosin Methylene Blue Agar media. Measurement of abiotic factors was on temperature and pH parameters. The test results of total coliform showed that 6 rivers contained total coliform under the Class II river water quality standards with a range of 1210/100 mL– 4310/100 mL and 2 rivers that were contaminated with Fecal coliform, TM and ALK, have the content of 1500/100 mL and 1700 / 100 mL. The results of the measurement of the abiotic factor, the river pH range was 7.4 - 8.2. The lowest temperature was 25oC in SPY river and the highest temperature was 26 oC on the TM, PP, EI, ALK, and ABB rivers.